Effect of soil type on seismic performance of reinforced concrete school building - Nur Amirah, Mohd Nasai (2017)
The nonlinear time history analysis simulates the response of building when subjected to real earthquake ground motion. Current practice only considers single earthquake in analysis. However, the tremors of earthquake always occur repeatedly for several times after the first one. This nature can be technically called as repeated or multiple earthquake. It also occurred during 2015 in Ranau, Sabah. The seismic performance of a building also influences by the soil type. The objective of this work is to study the effect of multiple earthquake and soil types on seismic performance of reinforced concrete school building. A total of two models of school building which have 2 and 4 storeys will be used in this work. The building is assumed to be located in Sabah. All models will be design based on BS8110 to represent the current RC school building. The nonlinear time history analysis has been conducted on both models using SAP2000. The single and multiple earthquakes has been considered in the analysis with two types of soil. The results are discussed in term of the lateral displacement at each storey and the interstorey drift ratio. In this study, the magnitude of interstorey drift ratio is increasing from the single earthquakes to the repeated earthquakes around 5.0% to 6.0%. Besides, the magnitude of interstorey drift ratio of models on Soil Type D which is around 14% higher than Soil Type B. Therefore, the effect of repeated earthquake and the soil type cannot be neglected for analysis and design in order to build safer structure in seismic region.